Pengaruh Penghindaran Pajak dan Arus Kas Bebas terhadap Manajemen Laba dengan Moderasi Kualitas Audit - Katry, Aulia Rachma; Sholihah, Ria Anisatus (Balance Vocation Accounting Journal, 2022)
Earnings management is managerial activity to influence and change some information of the financial report according to their needs until did not show the real condition. This study aims to examine the effect of tax avoidance and free cash flow on earnings management with audit quality as a moderating variable. The data in this study is from the financial statements of property, real estate, and building construction companies listed on the sharia stock for the period of 2015-2019. The sample used was 26 companies. The data analysis technique used is multiple linear regression and moderation test (subgroup) using Eviews version 10. The results showed that tax avoidance and free cash flow had a positive significant effect on earnings management. But, audit quality is not able to moderate the relationship between tax avoidance and free cash flow on earnings management.